A Prospective Study on 25 Hydroxyvitamin D Serum Levels in Patients with Relapsing-Remitting Multiple Sclerosis - Georgi Slavov; Maria Manova; Anastasiya Trenova; Ivanka Kostadinova; Pavel Pavlov; Nonka Mateva (Journal of Biomedical & Clinical Research, 2014)
To assess the changes in the serum concentrations of 25(ОH)D in relapse and remission and their relation to the degree of neurological deficit. We analyzed 53 subjects (30 controls and 23 patients) from October 2012 to Маy 2013. Diagnosis was based on McDonald 2010 criteria. The severity of neurological deficit was assessed by the Expanded Disability Status Scale. Serum concentrations of 25(ОH)D (nmol/l) were measured by ELISA once in controls and twice in patients - in relapse and remission. Mean levels in all groups were in the mild to moderate deficiency range, being lowest in the patients in relapse (controls 31.46±7.3; relapse 26.93±7.44; remission 28.06±7.28). There was a trend for lower levels of 25(ОH)D in healthy females in comparison to their male counterparts, and in female patients in relapse as compared to males (female controls - 26.56±8.4, male controls - 41.35±11.86; females in relapse - 26.33±10.03, males in relapse - 28.06±11.08). Negative statistically significant correlations between the concentrations of 25(ОH)D during relapse and remission and the degree of neurological deficit in the corresponding period were found (cc. -0.593, Sig 0.03, relapse; -0.46, Sig 0.024, remission). Assessment of the risk for development of MS, regarding the 25(ОH)D showed protective effect with respect to the risk of disease occurrence (ОR: 04125 relapse; 0.578 remission).